Limitations of a proper SFTSV mouse model using human C-type lectin receptors - Kim, You-Min; Ro, Hyo-Jin; Lee, Jae Hoon; Song, Yaechan; Lee, Han-Woong; Cho, Nam-Hyuk (Frontiers in Microbiology, 2024)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is a tick-borne virus with a human mortality rate of up to 30%, posing a significant threat to public health. However, the lack of suitable research models has impeded the development of effective human vaccines. In this study, we engineered transgenic mice (3xTg) using a novel construct that simultaneously expresses three C-type Lectin receptors, identified as critical SFTSV entry receptors. While this construct substantially enhanced viral binding and infection in BJAB cells, the 3xTg mice exhibited only limited SFTSV replication in the lymph nodes and spleen, without significant impacts on morbidity or mortality. These findings highlight that the overexpression of entry receptors alone is insufficient to fully recapitulate human SFTSV infection in mice. Moreover, our results reveal that the introduction of multiple entry receptors does not necessarily translate to enhanced infection efficacy. This underscores the need for further investigation into the interplay between SFTSV entry mechanisms and host factors to develop more robust mouse models. Advancing such models will be crucial for unraveling the pathogenesis of SFTS pathology and improving strategies for its prevention and treatment in humans.